Analyzing Behavioural Determinants for Perceived Risk of Heart Disease: Exploring Knowledge, Perceptions, and Behaviours related to Cardiovascular Disease (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Between and within nations, the burden of cardiovascular disease (CVD) varies substantially.Those in low- and middle-income countries (LMICs) and low- and middle-income groups (HGPCs) bear adisproportionate share of the burden (HIC).Few studies have examined how at-risk individuals view theirown and others' knowledge of, and exposure to, cardiovascular disease (CVD).Research on vulnerablepeople in Antwerp and Nottingham has been the subject of this project, as part of our study, we lookedat how much people knew about cardiovascular disease (CVD), their perceptions of risk, and theirintentions to become more active and eat healthily.In addition, we focused on Antwerp's widening socialdivide. So, this research is focused on the viewpoint of patients and the importance of health educationfor patients. Study's goal was to discover risk factors for CAD, as well as to determine whether patients'lives and habits have changed as a consequence of their illness. Cross-sectional study was conductedon 174 patients at Tertiary Care Hospital, Ashok Nagar utilizing a questionnaire including personal data,BMI, history of risk factors, behaviour change and medical advice. Epi Info examined the data andperformed the relevant statistical tests. Preventive measures should be prioritized, and people should becounselled before they get unwell as much as possible.